PRESYSIBILITY CONCEPT OF PRE-PROPOSED MAJAPAHIT CITY, ON MODERN REGULATION OF AREA CASE STUDY ON CAMPUS UI, UB AND ITB - Winarno (Jurnal Riset Arsitektur, 2018)
Abstract- Modern building design today has a tendency to focus only on the inner space, while the outer space only as space remaining from processing the space inside. Understanding of space in the context of modern-western architecture is certainly not necessarily in harmony with the understanding of space in the context of traditional Javanese architectureBased on the ongoing activities in traditional Javanese buildings, it shows the composition of spatial arrangement that allows interaction with the environment so that it is sustainable and responsive to nature / climate. The mass of the building can be seen as the visual boundary of the space marker, so it can be processed, among others, by given certain pressures such as the use of ornamentation, etc.According to Professor of Southeast Asian Archaeological National University of Singapore John N. Miksic the power of Majapahit range includes Sumatra and Singapore and even Thailand as evidenced by the influence of culture, building style, temple, sculpture and art. Trowulan itself is the capital and civilization center of Java Majapahit. Nagarakretagama mentions the palatial culture of a noble and elegant, with delicate artistry and literature, as well as a complicated religious ritual system. Majapahit temples good quality geometrically by utilizing the sap of vines and brown sugar as a brick adhesive. This style of building can still be found in Java and Bali architecture. In addition, Trowulan has a reservoir system called "Segaran", which functions as flood control and water source during drought. This research is trying to understand elements of ancient city of Trowulan and searching for the wealth of urban spatial Javanese - hindu this and looking for potential development in the present, The research will be done descriptively argumentative with qualitative approach through study on urban spatial Trowulan to modern area precedent.  Key Words: Urban Planning, Open Space, Majapahit Capital, Trowulan, Javanese- Hindu Civilization, Mandala